2004
DOI: 10.4049/jimmunol.172.8.4744
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Produced by Heme Oxygenase-1 Suppresses T Cell Proliferation via Inhibition of IL-2 Production

Abstract: Heme oxygenase-1 (HO-1) catabolizes heme into CO, biliverdin, and free iron and serves as a protective enzyme by virtue of its anti-inflammatory, antiapoptotic, and antiproliferative actions. Previously, we have demonstrated that human CD4+ T cells express HO-1 and that HO-1-overexpressing Jurkat T cells tend to display lower proliferative response. The aim of this study is to elucidate the mechanism(s) by which HO-1 can mediate its antiproliferative effect on CD4+ T cells. Among the three HO-1 byproducts, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
189
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(199 citation statements)
references
References 33 publications
7
189
1
2
Order By: Relevance
“…Little is known about how HO-1 expression in T cells affects their function. Pae et al have documented that CO produced by HO-1 activity in human T cells inhibited IL-2 secretion and proliferation [28]. HO-1 expression in effector T cells was also shown to induce Fas-mediated apoptosis [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about how HO-1 expression in T cells affects their function. Pae et al have documented that CO produced by HO-1 activity in human T cells inhibited IL-2 secretion and proliferation [28]. HO-1 expression in effector T cells was also shown to induce Fas-mediated apoptosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that miR-155-deficient splenic T cells exhibit a specific defect in IL-2 production following antigenic stimulation [12]. Interestingly, HO-1 expression in T cells has previously been reported to inhibit IL-2 production directly or by inducing apoptosis of IL-2-producing cells [28,29]. We then set up experiments aimed at analyzing how HO-1 inhibition could affect IL-2 secretion by miR-155 −/− T cells.…”
Section: Inhibition Of Ho-1 Promotes Tissue Inflammation By Adaptivelmentioning
confidence: 99%
“…The exact role of HO-1 expression is not fully understood in T-cells. However, growing evidence has shown that HO-1 and its byproduct, CO, suppress T-cell proliferation [34,35]. The over-expression of HO-1 results in the inhibition of several immune effector functions and thus provides an explanation for stressinduced immunosuppression [36].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 induction leads to the suppression of T cell proliferation and IL-2 secretion and to the inhibition of class II major histocompatibility complex molecule expression in antigen-presenting cells (23,24). In addition, HO-1 expression occurs in Treg cells in a manner analogous to their specific transcription factor FoxP3 (3).…”
Section: Discussionmentioning
confidence: 99%